Gender differences and left-behind experiences in the relationship between gaming disorder, rumination and sleep quality among a sample of Chinese university students during the late stage of the COVID-19 pandemic - Li, Li; Liu, Ligang; Niu, Zhimin; Zhong, Huahua; Mei, Songli; Griffiths, Mark D. (Frontiers in Psychiatry, 2023)
Background and aims Studies have shown that gaming disorder (GD) is associated with rumination and poor sleep quality. However, the reciprocal relationship between GD, rumination and sleep quality is unclear. Moreover, the differences between gender and between left-behind experiences in the aforementioned relationship remain unknown. Therefore, the present study examined gender differences and left-behind experiences in the relationship between GD, rumination, and sleep quality among a sample of Chinese university students during the late stage of COVID-19 pandemic using a network analysis approach. Methods A cross-sectional online survey of 1,872 Chinese university students was conducted comprising demographic information (age, gender, and left-behind experience), gaming experience, gaming frequency, Gaming Disorder Test (GDT), Short Version of Rumination Response Scale (RRS), and Pittsburgh Sleep Quality Index (PSQI). Results Among Chinese university students, the prevalence of (i) GD was 3.5% and (ii) sleep disturbance was 14%. GD had positive and weak connection with rumination and sleep quality in the domain-level relational network. The network structures and global strengths both showed no significant differences between gender and between left-behind experiences. The nodes gd3 (“continuation or escalation of gaming”) and gd4 (“gaming problems”) had the strongest edge in the network. Conclusion The results suggest reciprocal relationships between GD, rumination, and sleep quality. Gender and left-behind experiences did not influence the reciprocal relationship between GD, rumination, and sleep quality during the late stage of COVID-19 pandemic. Using network analysis, the findings provide novel insights that rumination and sleep quality may have interacted with GD among Chinese students during the late stage of COVID-19 pandemic. Reducing or eliminating negative rumination may decrease GD and improve sleep quality. Moreover, good sleep quality contributes to positive rumination which may decrease the risk of GD among Chinese university students.